Operational performance of hollow fibre for water treatment system - Rosdianah Ramli (2017)
Innovation such as mobile water treatment unit brings water treatment system to a new level of convenience for its user, especially in rural areas. Having compact and self-supporting configuration, hollow fibre membrane became a choice as a filter media for mobile water treatment system. In this study, polyvinylidene fluoride (PVDF) ultrafiltration hollow fibre (UF-HF) membrane module was designed for application in mobile water treatment unit system; catering for domestic and lightweight surface water treatment based on prime feature of a common mobile water treatment system. Two types of UF-HF membrane modules were prepared with two different number of fibre i.e. 15 and 30 fibres, resulting in effective membrane areas of 0.0153m2 and 0.0305m2 . A UF-HF membrane module was integrated in membrane testing rig operated under varying transmembrane pressure (TMP), feed water temperature, and feed water quality (turbidity). It was found that the optimum TMP is between 2.8 to 3.2 bars while the module performed steadily at temperature of 22 to 27 ° C. At varying feed water quality, both modules were able to remove 96% turbidity regardless of the initial turbidity value. In a short-term operation of surface water treatment, a maximum of 0.073 L/min filtered water was able to be produced by a UF-HF membrane module while the recorded specific permeate flux dropped at 33% at the end of the operation. Water recovery recorded was below 10% with the energy consumption of 41 %. This reduces the possibility of concentration polarisation on the membrane module. Moreover, the UF-HF membrane module had shown good treatment efficiency for surface water where total suspended solids were removed completely, plus more than 30% of biochemical oxygen demand, chemical oxygen demand, and ammoniacal nitrogen. Dissolved oxygen and pH were enhanced by more than 5%. In conclusion, the designed UF-HF membrane module can be upgraded for the use of water treatment system in rural areas.